Analysis of the Mechanical Properties of Teak Sawdust-Reinforced Composite Boards Affected by the Alkalization Process - Reza Putra; Muhammad Muhammad; T Hafli; Nurul Islami; Muhammad Nugraha P; M Irsyad K (International Journal of Engineering, Science and Information Technology, 2022)
The development of the teak wood processing industry is growing rapidly, especially in the Aceh area. Allows a lot of waste to be generated. This research was conducted by utilizing sawn wood waste into particle boards. To test the physical and mechanical properties of particleboard using a matrix of teak waste and SHCP 2668 WNC resin with a ratio of 60: 40, and variations in treatment (NaOH) 2,5, 5, and 7,5% in immersion for 2 hours. Then the particleboard is compressed using a hot press machine at a temperature of 150˚C for 20 minutes, and a pressure of 50 kg/cm2. Then tested according to SNI 03-2105-2006 standards, namely density, thickness expansion, moisture content, elasticity, and modulus of fracture. The results of the particle board test on the physical and mechanical properties test, namely the density yielded the best value for the 5% (NaOH) treatment with a value of 0.854 gr/cm3, the best water content test with 2.5% (NaOH) treatment with a value of 4.563 %, viscous development with treatment (NaOH) 5% with a value of 7.573%, the best elasticity test on treatment (NaOH) 2.5% with a value of 2.470 kgf/cm2, and the best fracture modulus test on treatment (NaOH) 7.5% with a value of 48.611 kgf/cm2 declared to meet the standard requirements of SNI 03-2105-2006. With alkaline treatment, particleboard gives a relatively good value compared to no treatment.